LEGAL SHORTCOMINGS OF ACCOUNTING FOR LEASING OPERATIONS IN THE LEGISLATION OF THE REPUBLIC OF AZERBAIJAN AND PROPOSALS FOR THEIR SOLUTION - Shafa Guliyeva (Правові горизонти, 2023)
The article discusses the features of leasing operations in the Republic of Azerbaijan. The focus is on the regulatory and legal aspects of the control of leasing operations. An attempt has been made to identify the existing shortcomings, analyse them, and on this basis formulate proposals for their elimination. The normative legal documents of the Republic of Azerbaijan and other states are used in the work. As a result of the study, the peculiarities of the regulation of leasing operations are revealed, the prospects for the development of this direction in Azerbaijan are determined. In addition, this article examines the history of the introduction of the leasing agreement into Azerbaijan legislation, as well as some practical aspects of its formation. A comparative analysis of the current legislation with the previous one regulating the procedure for concluding and executing this agreement and considering it as a special type of services is carried out. The article also notes that in practice, erroneous attempts were made to fit leasing under a loan agreement, which does not correspond to its legal nature. The relevant Resolution of the Constitutional Court of the Republic of Azerbaijan is analysed in this issue. The article classifies the forms of the leasing agreement and reveals its content with reference to legislation, legal literature, as well as judicial practice. In the next few years, the leasing market should expect significant recovery growth. The article tackles the main shortcomings of the legislation regulating relations in the field of leasing relations and provides proposals for their elimination. The relevance of the article lies in the fact that in the coming years, the leasing market should expect significant recovery growth, for which leasing companies and their clients need government support not only in subsidizing, but also in improving the legislative framework.